Pengaruh Kepercayaan, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Internet Di Kota Makassar - Sukawati, Sukawati (Universitas Negeri Makassar, 2018)
The research aims to study how consumers make buying decisions through the internet which is influenced by trust, price, and product quality. The research is quantitative descriptive research. The populations of the research were the residents of Makassar City who shopped through the internet. The samples were taken by using non probability sampling technuque by using incidental sampling method with one hundred samples. The data analysis of the research employed multiple regression analysis which consisted of t test (partial) and F test (simultaneous) toward research variables. The results of the research reveal that (i) patially, trust has significant influence toward buying decision through the internet in Makassar City. Trust is the main factor tha someone must have to make buying decision through the internet; (ii) partially, price has significant influence toward buying decision through the internet in Makassar City. Product price has important role in the determination process of buying decision in the determination process of buying decision; (iii) partially, product quality gives no significant influence toward buying decision through the internet in Makassar City. Product quality gives no influence to the consumers to shop through the internet; (iv) simultaneously, trust, price, and product quality have significant influence toward buying decision through the internet in Makassar City.